A novel indolo[3, 2-b]carbazole derivative with D-π-A structure exhibiting aggregation-enhanced emission and mechanofluorochromic properties. (December 2018) - Zhang, Yuyang; Ma, Yuqing; Kong, Lin; Tian, Yupeng; Yang, Jiaxiang
Abstract: A novel symmetrical indolo[3, 2- b ]carbazole derivative (ICZ-CN ) containing dicyanovinyl groups has been designed and synthesized. The typical D-π-A type conjugated compound exhibited an obvious intramolecular charge transfer (ICT) property, which was evidenced by UV-vis absorption, fluorescent emission spectroscopy and density functional theory (DFT) calculations. Meanwhile, ICZ-CN exhibited a strong aggregation-enhanced emission (AEE) characteristic. Interestingly, compound ICZ-CN showed a reversible mechanofluorochromic (MFC) property between yellow and orange-red emission by grinding-fuming processes. The MFC mechanism was investigated through the single crystal structure, the scanning electron microscope (SEM) and the powder X-ray diffraction (XRD). The results showed that the mechanofluorochromic property is attributed to the loose molecular packing by weak intermolecular hydrogen bond interactions was destroyed and generated the phase transformation from crystalline to amorphous states under external stimulations. The results would be of great help in understanding and designing new MFC materials. Graphical abstract: A novel D-π-A structure indolo[3, 2- b ]carbazole derivative exhibiting aggregation-enhanced emission and mechanofluorochromic properties in solid state. Image 1 Highlights: A novel indolo[3, 2- b ]carbazole derivative (ICZ-CN ) has been designed and synthesized. ICZ-CN exhibited obviously intramolecular charge transfer and aggregation-enhanced emission characteristic. ICZ-CN showed a reversible mechanofluorochromic property between the crystalline and the amorphous states.